1997
DOI: 10.1073/pnas.94.5.1755
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional arrest: Escherichia coli RNA polymerase translocates backward, leaving the 3′ end of the RNA intact and extruded

Abstract: RNA polymerase (RNAP) may become arrested during transcript elongation when ternary complexes remain intact but further RNA synthesis is blocked. Using a combination of DNA and RNA footprinting techniques, we demonstrate that the loss of catalytic activity upon arrest of Escherichia coli RNAP is accompanied by an isomerization of the ternary complex in which the enzyme disengages from the 3 end of the transcript and moves backward along the DNA with concomitant reverse threading of the intact RNA through the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
321
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(339 citation statements)
references
References 25 publications
(71 reference statements)
17
321
1
Order By: Relevance
“…These inactive/stalled TCs can be reactivated by the addition of Gre factors and may thus correspond to previously described dead end or arrested complexes (3,12,13,39). When analysis similar to the one described above was performed with several templates driven by well studied E. coli RNAP promoters such as T7 A1, rrnB P1, and T5 N25, no stalled or arrested promoter-proximal TCs that were sensitive to Gre factors could be detected (data not shown).…”
Section: Stable Inactive Promoter-proximal Transcription Elongation Csupporting
confidence: 73%
See 3 more Smart Citations
“…These inactive/stalled TCs can be reactivated by the addition of Gre factors and may thus correspond to previously described dead end or arrested complexes (3,12,13,39). When analysis similar to the one described above was performed with several templates driven by well studied E. coli RNAP promoters such as T7 A1, rrnB P1, and T5 N25, no stalled or arrested promoter-proximal TCs that were sensitive to Gre factors could be detected (data not shown).…”
Section: Stable Inactive Promoter-proximal Transcription Elongation Csupporting
confidence: 73%
“…Inactive/Stalled Promoter-proximal TCs Formed on PrplN and PompX Are backtracked-Previously characterized arrested TCs were shown to form when the RNAP catalytic center disengages from the 3Ј end of the nascent transcript and the enzyme backslides along the DNA (12,13). The "extra" RNA proximal to the 3Ј end is likely accommodated in the RNAP secondary channel, which also accepts the transcript cleavage factors (28,40).…”
Section: Stable Inactive Promoter-proximal Transcription Elongation Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that we have not formally excluded the possibility that interactions between RNA and polymerase may also contribute to the energy barrier to backward movement of the enzyme during backtracking; however, it has been shown that addition of oligonucleotides complimentary to regions of the nascent RNA attenuates backtracking and stabilizes active transcription (33). This observation runs contrary to what one would expect if the mechanism of pause attenuation were mediated through RNA/protein interactions, as hybridization with the oligonucleotides would presumably compete with the RNA/protein interactions.…”
Section: Resultsmentioning
confidence: 93%